Islam Nusantara and the Challenges of Political Islam in the Contemporary World: Emphasizing the views of Abdurrahman Wahid - Esfandiar, Mahmoodreza (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2022)
This article examines the principal challenges faced by Islam Nusantara in its engagement with political Islam in the contemporary global context. The study aims to analyze the historical formation and intellectual characteristics of three major currents of Islamic thought in Indonesia, traditional Islam, religious reformism, and liberal Islam, and to assess their respective responses to modern political and theological contestations. Methodologically, the research employs a qualitative, historical-analytical approach, combining intellectual history with discourse analysis. It traces the transregional networks linking the Malay-Indonesian archipelago to major Middle Eastern centers such as Mecca, Medina, and Cairo, while examining the internal dynamics of pesantren-based traditionalism and reformist-modernist movements. Particular attention is given to the intellectual influence of modern Muslim thinkers, including Fazlur Rahman, and to the socio-religious thought of Abdurrahman Wahid. The findings demonstrate that Indonesian Islamic reformism emerged through sustained engagement with Middle Eastern reformist discourses, whereas traditional Islam represents a localized synthesis of Shāfiʿī jurisprudence, Ashʿarī theology, and Sufi traditions embedded in the archipelago’s socio-cultural matrix. Liberal Islam further rearticulated Islamic intellectualism in dialogue with modern hermeneutics and democratic values. The study shows that Islam Nusantara offers a mediating framework that reconciles tradition and reform, countering exclusivist strands of political Islam. The article concludes that Islam Nusantara, particularly as articulated in Wahid’s thought, provides a viable normative and cultural paradigm for pluralism, democratic coexistence, and crisis resolution in contemporary Muslim societies.